High-Energy Flux Density Extracorporeal Shock Wave Therapy Versus Traditional Physical Therapy Modalities in Myofascial Pain Syndrome: A Randomized-controlled, Single-Blind Trial - Ömer GEZGİNASLAN and Sevgi GÜMÜŞ ATALAY (Archives of Rheumatology, 2020)
Objectives: This study aims to investigate the effects of extracorporeal shock wave therapy (ESWT) on pain, sleep, fatigue, disability, depression, and quality of life (QoL) in patients with myofascial pain syndrome (MPS). Patients and methods: Between March 2018 and September 2018, a total of 94 patients (16 males, 78 females; mean age 44.2±11.94 years; range, 19 to 74 years) with the diagnosis of MPS were included in the study. The patients were divided into two groups. The treatment group consisted of 49 patients and a total of seven sessions of high-energy flux density ESWT (H-ESWT) (0.26 mJ/mm2) were given with three days interval. The control group consisted of 45 patients and the treatment of hot pack, transcutaneous electrical nerve stimulation, and ultrasound was given for five days for two weeks. At baseline and one month after treatment, the visual analog scale (VAS), Short Form-36 (SF-36), Pittsburgh Sleep Quality Index (PSQI), Functional Assessment of Chronic Illness Therapy (FACIT)-Fatigue Scale, Neck Disability Index (NDI), and Beck Depression Inventory (BDI) scores were compared between the groups. Results: There were no statistically significant differences in the age, sex, demographic characteristics, and baseline VAS, SF-36, NDI, BDI, FACIT, and PSQI scores between the groups (p>0.05). In the ESWT group, there was a statistically significant decrease in the VAS, SF-36, NDI, BDI, FACIT, and PSQI scores after treatment compared to the baseline scores, while only the SF-36 subscale scores were statistically significantly higher (p<0.05). There was a statistically significant correlation between the VAS and SF-36 scores and the BDI, NDI, FACIT and PSQI scores after the treatment. Conclusion: Our study results suggest that H-ESWT is more effective than traditional physical therapy methods on pain, QoL, sleep, fatigue, depression, and disability in patients with MPS.